Semantics and expressive power of subqueries and aggregates in SPARQL 1.1 - Kaminski, M; Kostylev, E; Cuenca Grau, B (Association for Computing Machinery, 2015)
Answering aggregate queries is a key requirement of emerging applications of Semantic Technologies, such as data warehousing, business intelligence and sensor networks. In order to fulfill the requirements of such applications, the standardisation of SPARQL 1.1 led to the introduction of a wide range of constructs that enable value computation, aggregation, and query nesting. In this paper we provide an indepth formal analysis of the semantics and expressive power of these new constructs as defined in the SPARQL 1.1 speci- fication, and hence lay the necessary foundations for the development of robust, scalable and extensible query engines supporting complex numerical and analytics tasks.